INNOVATIONS IN CERVICAL CANCER THERAPY: THE IMPACT OF IMMUNOTHERAPY ON HEALTH SYSTEMS AND EDUCATION - Paulina Redel; Aleksandra Dzwonkowska (International Journal of Innovative Technologies in Social Science, 2025)
Cervical cancer is one of the most common genital malignancies in women worldwide, although its development is largely preventable through effective primary and secondary prevention programs. The main cause of the development of this cancer is chronic infection with oncogenic types of human papillomavirus (HPV), particularly types 16 and 18. The introduction of HPV vaccination and regular screening (cytology, HPV DNA testing) has significantly contributed to the decline in incidence in developed countries. Unfortunately, in many regions of the world, including Poland, vaccination and screening rates remain inadequate, resulting in a high incidence and death rate. The standard treatment for locally advanced cervical cancer is combination chemoradiotherapy, which combines radiotherapy with the simultaneous administration of cisplatin. In recurrent and metastatic cases, where radical treatment is not possible, systemic treatment is used - mainly chemotherapy based on a combination of cisplatin and paclitaxel, often with the addition of bevacizumab, an angiogenesis inhibitor. Advances in targeted therapies and immunotherapies (e.g., PD-1/PD-L1 checkpoint inhibitors) are opening up new therapeutic options, increasing the chances of prolonging survival and improving quality of life for patients with advanced disease. Numerous clinical trials are currently underway to evaluate the efficacy of new drugs and combination treatment strategies. There is also a growing emphasis on personalizing therapy based on molecular biomarkers. Effective control of cervical cancer requires an integrated approach - combining prevention, early detection, and access to modern treatments. The future of the fight against this cancer involves global implementation of HPV vaccination, expansion of screening programs, and development of precision systemic therapies. This review synthesizes the current state of knowledge, challenges, and new directions in the prevention, diagnosis, and treatment of cervical cancer.